An alternative approach for determining the effective atomic number of some compounds: Monte Carlo study - Ozsahin, M. T.; Kalecik, S.; Toker, O.; Kurucu, Y.; Icelli, O. (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Researchers have been searching for different methods to determine the effective atomic number of materials for many years. Therefore, there are many methods in the literature to determine the effective atomic number theoretically or experimentally. While theoretical methods neglect some parameters, such as the momentum transfer parameter, photon energy, or scattering angle, experimental methods have incommodious processes. The main goal of this study is to provide a practical simulation method that is both as realistic as experimental results and as easy as theoretical methods. The method considers all these parameters compared to other theoretical methods and transfers them to the virtual environment. In this study, Rayleigh and Compton scattering peaks of 60 pure elements (in the range 20< Z <80) were determined. Rayleigh and Compton peak ratios were correlated with their atomic numbers. The proposed method is available for any energy or scattering angle. Six different compounds (WC, W65Cu35, SnAg, Fe54Co17Ni29, Pd94Cr6, Cu60Zn40) were selected from different atomic number regions (such as low, medium, and high regions). It is important to note that any material (compound or mixture) could be selected. Validation of the method has been performed via different methods commonly used in the literature. It is observed that the results of this method are in good agreement with other methods in the literature. We are expecting that the proposed method will provide great convenience and guidance to researchers in this area.
Keywords: Effective atomic number; Rayleigh scattering; Compton scattering; Monte Carlo simulation; INELASTIC-SCATTERING; RADIATION; RAYLEIGH; Chemistry; Nuclear Science & Technology; Physics